(untitled) (Journal of Atomic and Molecular Sciences, 2012)
The differential and integral cross sections for the excited states 1s2p ^3P, 1s3s ^3S, 1s3p ^3P and 1s3d ^3D of helium from the metastable state 1s2s ^3S are calculated using the relativistic distorted wave method. A systematical comparison is made with the available experimental and theoretical results. Better agreement is found when the present results are compared with previous calculations and experiments for the integral cross sections. For differential cross sections, our results are in general agreement with the experimental data compared with the previous theoretical values.